Montaje y programación de una central telefónica modelo Panasonic kx-tes824 con fines didácticos para el laboratorio de telecomunicaciones de la Universidad Nacional de Loja. - Barrera Ramos, Milton Renato (2011)
Our research is SCHEDULE A RIDE AND CENTRAL TELEPHONE PANASONIC KX-TES824 MODEL EDUCATIONAL PURPOSES TELECOMMUNICATIONS LABORATORY OF THE NATIONAL UNIVERSITY OF LOJA The KX-TES824 is a phone system that can handle business and personal needs. The KX-TES824 supports 3 outside lines and 8 extensions. With optional cards can easily expand your system capacity up to 8 lines and 24 extensions, depending on the needs increase. The Central is ideal for homes, offices and small businesses that require flexible communication system. This can connect a variety of communication equipment such as: multi-line phones, wireless modems, answering machines, credit card terminals, fax, intercom and video intercom. Also peripheral systems such as: rates of calls, voice mail, counter flashing electrical or magnetic, electric gates, among others. Mounted and programmed the phone system Panasonic KX-TES824 model with the success expected to understand the functions and features according to the diagram proposed to be easy to understand for students. Was successful connection of the telephone and took practice tests with students in sixth module of the career of electronic technology.